Analisis Implementasi Sistem Distribusi Dalam Menjaga Keseimbangan Permintaan Dan Penawaran Produk Pertanian Kakao Di Pesawaran, Provinsi Lampung - Galih Dwi Saputra; Erlin Kurniati (SUAN PUBLISHER, 2025)
This study aims to analyze the implementation of the distribution system of cocoa agricultural products in Pesawaran Regency, Lampung Province, with a focus on maintaining a balance between market demand and supply. The research employs a qualitative approach using descriptive methods, involving interviews, field observations, and documentation of insights from distribution actors, cocoa farmers, and other relevant stakeholders. Findings reveal that the current distribution system largely relies on conventional practices, which tend to be inefficient and inadequate in addressing rapid market changes. Key structural issues—including limited infrastructure, low accessibility to market information, and underdeveloped distribution institutions—continue to hinder responsiveness and scalability. As a result, farmers and small-scale distributors often struggle to meet quality standards and market expectations. To address these challenges, the study underscores the need to implement a more technology-driven distribution mechanism, incorporating digital platforms and logistical innovations to streamline supply chains. Additionally, collaborative efforts among stakeholders such as cooperatives, government agencies, and private sector actors are essential to create a more adaptive and inclusive distribution system. These improvements aim not only to enhance operational efficiency but also to ensure long-term sustainability by reinforcing the local cocoa industry's resilience. Ultimately, the research recommends strategic policy support and coordinated multi-stakeholder engagement to establish a distribution framework that fosters competitiveness while preserving supply-demand equilibrium.